The harmonisation of rules on the recognition and enforcement of foreign judgments in the Southern African Customs Union - Mandi Rossouw (Pretoria University Law Press (PULP), 2016)
About the publication While the harmonisation of the rules on the recognition and enforcement of foreign judgments has been given priority in other regional economic communities, in particular the European Union, any similar effort to harmonise the rules on recognition and enforcement of member states has been conspicuously absent in the SACU, and in fact the most of the African continent - a situation which needs to receive immediate attention. This book considers the approaches followed by a number of international and regional organisations, including the EU, the USA, Australia and New Zealand and Latin American States, with a view to identifying the most suitable approach to be adopted for the SACU. Table of Contents Foreword Introduction and background 1 Introduction 2 Key concepts 2.1 Regional economic integration 2.2 The Southern African Customs Union 2.3 Private international law 2.4 Recognition and enforcement of foreign judgments 2.5 Harmonisation 3 Origin and background of study 3.1 The lack of global recognition and enforcement regime 3.2 The lack of a regional recognition and enforcement regime 3.3 International developments in the field 3.4 Regional integration on the African continent 4 Rationale for the study 4.1 Trade facilitation 4.2 Facilitation of regional economic integration 5 Framework of analysis 5.1 Territorial sovereignty, obligation theory, comity and reciprocity 5.2 States' interest in recognising and enforcing foreign judgments 6 Research questions 7 Scope and exclusions from scope 8 Chapter outline Recognition and enforcement of foreign judgments - overview of international and regional harmonisation efforts 1 Introduction 1.1 Bilateral treaties as means of harmonising enforcement rules 1.2 Multilateral conventions as means of harmonising recognition and enforcement rules 2 Harmonisation of recognition and enforcement of foreign judgments at the international level 2.1 The Hague Conference on Private International Law 2.2 Some other intergovernmental and private organisations 2.3 Evaluation of international harmonisation efforts 3 Harmonisation of recognition and enforcement of foreign judgments at the regional level 3.1 European community Brussels/Lugano Regime 3.2 United States full faith and credit approach 3.3 The Trans-Tasman judicial area 3.4 Latin American states 4 Feasibility of the different approaches for the SACU 4.1 Brussels/Lugano regime 4.2 United States of America full faith and credit approach 4.3 Trans-Tasman Judicial System 4.4 Latin America 5 Proposed approach for the SACU 6 Some factors likely to influence harmonisation in SACU 7 Concluding remarks Comparison of multilateral conventions on the recognition and enforcement of foreign judgments 1 Introduction and overview of types of multilateral recognition and enforcement conventions 1.1 Single convention 1.2 Double convention 1.3 Analysis 1.4 Variations on traditional convention types 2 The Hague Convention on Recognition and Enforcement 2.1 Material scope of application of Convention 2.2 Procedural requirements for enforcement 2.3 Grounds for non-recognition 3 The Hague Choice of Court Convention 3.1 Material scope of application of Convention 3.2 Procedural requirements for recognition and enforcement 3.3 Grounds for non-recognition 4 The EU Brussels Convention/Regulation 4.1 Material scope of application of Convention/ Regulation 4.2 Procedural requirements for recognition and enforcement 4.3 Grounds for non-recognition 5 The Montevideo Convention 5.1 Material scope of application of Convention 5.2 Procedural requirements 5.3 Grounds for non-recognition 6 Overview of the Conventions discussed 6.1 Hague Convention on Recognition and Enforcement of Foreign Judgments 6.2 Hague Choice of Court Convention 6.3 EU Brussels Regulation/Convention 6.4 Montevideo Convention 7 Concluding remarks Comparison of Existing Laws on Recognition and Enforcement of Foreign Judgments in the SACU and Proposals for Draft Convention 1 Introduction 2 Recognition and enforcement under the common law tradition 2.1 Administration of Justice Act, 1920 2.2 Foreign Judgment (Reciprocal Enforcement) Act, 1933 3 Overview of relevant statutes 3.1 Swaziland 3.2 Lesotho 3.3 Botswana 3.4 South Africa 3.5 Namibia 4 Comparative analysis 4.1 Scope of application 4.2 Requirements for enforcement 4.3 Procedural requirements 4.4 Setting aside of registered judgments 4.5 International competence 4.6 Other matters the Convention may include 5 Proposed text for a convention on the recognition and enforcement of foreign judgments 6 Conclusion The recognition and enforcement of foreign judgments - conclusions 1 Introduction - The need for a harmonised recognition and enforcement regime 2 International and regional harmonisation efforts 3 Overview of some of the major multilateral recognition and enforcement instruments 4 Statutory instruments currently in force in the SACU 5 Final comments Bibliography